Pharmacokinetic-Pharmacodynamic Analysis on Inflammation Rat Model after Oral Administration of Huang Lian Jie Du Decoction - Ren, Wei (PLoS One, 2016)
Huang-Lian-Jie-Du Decoction (HLJDD) is a classical Traditional Chinese Medicine (TCM) formula with heat-dissipating and detoxifying effects. It is used to treat inflammation-associated diseases. However, no systematic pharmacokinetic (PK) and pharmacodynamic (PD) data concerning the activity of HLJDD under inflammatory conditions is available to date. In the present study, the concentration-time profiles and the hepatic clearance rates (HCR) of 41 major components in rat plasma in response to the oral administration of a clinical dose of HLJDD were investigated by LC-QqQ-MS using a dynamic multiple reaction monitoring (DMRM) method. Additionally, the levels of 7 cytokines (CKs) in the plasma and the body temperature of rats were analyzed. Furthermore, a PK-PD model was established to describe the time course of the hemodynamic and anti-inflammatory effects of HLJDD. As one of the three major active constituents in HLJDD, iridoids were absorbed and eliminated more easily and quickly than alkaloids and flavonoids. Compared with the normal controls, the flavonoids, alkaloids and iridoids in inflamed rats exhibited consistently changing trends of PK behaviors, such as higher bioavailability, slower elimination, delays in reaching the maximum concentration (T(max)) and longer substantivity. The HCR of iridoids was different from that of alkaloids and flavonoids in inflamed rats. Furthermore, excellent pharmacodynamic effects of HLJDD were observed in inflamed rats. The levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), IL-1β, IL-10, and macrophage inflammatory protein-2 (MIP-2) and body temperature significantly decreased after the administration of HLJDD. Based on PK-PD modeling with the three-phase synchronous characterization of time-concentration-effect, flavonoids exhibited one mechanism of action in the anti-inflammatory process, while iridoids and alkaloids showed another mechanism of action. Taken together, the results demonstrated that HLJDD may restrain inflammation synergistically via its major constituents (alkaloids, flavonoids and iridoids). A correlation between the exposure concentration of different types of compounds and their anti-inflammatory effects in the body was shown. This study provides a comprehensive understanding of the anti-inflammatory activity of HLJDD.